Six sigma methodology restructuring the trainig and development process of the organization and application - Kısakürek, İrem (My University, 2005)
SIX SIGMA METHODOLOGY RESTRUCTURING THE TRAINING AND DEVELOPMENT PROCESS OF THE ORGANIZATION AND AN APPLICATION The primary reason training is considered optional by so many business owners is because it's viewed more as an expense than an investment. This is completely understandable because finding out the profit of training is hard because measuring the effectiveness of the process is undefinable. Without measurable results, it's almost impossible to view training as anything more than an expense. In today's economy, if your business isn't learning, then you're going to fall behind. Business learns as its people learn. The employees are the ones that produce, refine, protect, deliver and manage the business. With the rapid pace and international reach of the 21st century marketplace, continual learning is critical to the business's continued success. This is a descriptive study which is a result of literal research defines the way of creating an effective process of training and development by using Six Sigma Methodology and shows the example of designing the process. Soyadı: İrem Kısakürek Anabilimdalı: Kamu Yönetimi Human Resources Management and Development Yard.Doç.Dr. Ahmet Tuğrul Savaş Tez Türü ve Tarihi: Yüksek Lisans - Ağustos 2005 Altı, Sigma, Eğitim, Gelişim, Yapılandırma

ORGANİZASYONUN EĞİTİM VE GELİŞİM SÜRECİNİN YENİDEN YAPILANDIRILMASINDA ALTI SİGMA METODOLOJİSİ VE BİR UYGULAMA Eğitimin bir gerek olarak değil de keyfi bir aktivite olarak algılanmasının altında yatan temel neden, bu aktivitenin bir yatırım olarak değil bir maliyet unsuru olarak algılanmasında yatmaktadır. Bu tamamen anlaşılabilir bir nedendir, eğitimin verimliliğinin ölçülmesinin tanımlanamamış olması sebebiyle, getirisinin ortaya konması oldukça zordur. Ölçülemeyen sonuçlarla da eğitimi bir maliyet unsuru olarak algılamaktan fazlası yapılamaz. Bugünün ekonomisinde eğer işiniz öğrenmiyorsa rakiplerinizden geriye düşmeniz kaçınılmazdır. Bir iş, ancak o işi yapan insanlar öğreniyorsa, öğrenebilir. Çalışanlar, işi, üreten, inceleştiren, koruyan, yerine getiren ve yönetenlerdir. Yirmibirinci yüzyılın dörtnala koşan uluslararası piyasa koşullarında sürekli öğrenme işin süreğen başarısı için kritiktir. Literatür taraması neticesinde ortaya çıkan açıklayıcı türdeki bu çalışma, Altı Sigma Metodolojisi kullanılarak, verimli bir eğitim ve gelişim sürecinin yapılandırılışını bir örnek ile ortaya koyarak yansıtacaktır.
Keywords: İnsan Kaynakları